ESTUDOS DE LINGUA(GEM) E RACISMO - Nascimento, Gabriel; Souza Neto, Mauricio José; Thomaz de Aquino Martins, Suellen (Estudos Linguísticos e Literários, 2024)
Apresentação do dossiê Linguagem e Racismo.